TÓPICOS DE FÍSICA MODERNA NO ENSINO MÉDIO SOB UMA PERSPECTIVA DO NANOMAGNETISMO - Silva, ícaro Ilo da (2011)
This work had as objective the elaboration and organization of a set of didactic materials that had come to constitute a Didactic Module, associating topical of Modern Physics, magnetism and Nanoscience for the proposal of the education of the Nanomagnetism for students of High School. The methodology involves the accomplishment of empirical research (questionnaire-sounding), theoretician-bibliographical study on the subject and elaboration of a didactic proposal. The Didactic Module makes use of texts of literature and the hypermedia resource, where texts, images, videos and animations are presented. To give credit to the proposal, three questionnaires had been applied: the first one for students of a group of third year of High School in intention to check the previous knowledge of basic concepts related to the subject and its interest in learning more; the second, for participants of a course in event of Physics education; the third, for another group of students of the third year of High School, after application of the elaborated hypermedia that constitutes central material of the Didactic Module. Of the first one, we can observe great difficulties in the understanding and knowledge of basic concepts on the part of the students group, and at the same time its interest for the subject. In the second, answered for a majority of students of formation course of teachers and also for after-graduated students, it is distinguished an enormous acceptance of the subject and valuable contributions for the Didactic Module. Of third, new acceptance of the subject, verified for the attention and participation of the group during the boarding of the subject and its answers to the questionnaire. It is given credit to have fulfilled the mission to construct and to show a source of pedagogical resource that can contribute for one better quality of the process teach-learning of Physics.